2D crystals of transition metal dichalcogenide and their iontronic functionalities. (13th October 2015) - Zhang, Y J; Yoshida, M; Suzuki, R; Iwasa, Y
Abstract: 2D crystals based on transition metal dichalcogenides (TMDs) provide a unique platform of novel physical properties and functionalities, including photoluminescence, laser, valleytronics, spintronics, piezoelectric devices, field effect transistors (FETs), and superconductivity. Among them, FET devices are extremely useful because of voltage-tunable carrier density and Fermi energy. In particular, high density charge accumulation in electric double layer transistor (EDLT), which is a FET device driven by ionic motions, is playing key roles for expanding the functionalities of TMD based 2D crystals. Here, we report several device concepts which were realized by introducing EDLTs in TMDs, taking the advantage of their extremely unique band structures and phase transition phenomena realized simply by thinning to the monolayer level. We address two kinds of TMDs based on group VI and group V transition metals, which basically yield semiconductors and metals, respectively. For each system, we first introduce peculiar characteristics of TMDs achieved by thinning the crystals, followed by the related FET functionalities.